Surface electromyography and force production of a novel strength training method suitable for microgravity - Fisher, J.; Steele, J.; Jessop, D. (Journal of Trainology, 2016)
Objectives: Current protocols for resistance training in space flight are hindered by size, mass, noise, vibration and cost, and potentially still lack efficacy. The purpose of the present study was to examine the muscle activation and force output for con tralateral limb resisted training compared to traditional resistance training with a view towards the practicality of use in microgravity environments. Design: Following ethical approval, employing a within-subject design 12 healthy, resistance-trained males performed a 1-repetition maximum bench press (BP) and three isometric tests at differing elbow joint angles (ISO45°, ISO90°, ISO135°) using a Micro-Gym device. Methods: Surface electromyography (sEMG) was used to assess peak amplitude of the pectoralis major (PM), anterior deltoid (AD) and triceps brachii (TB) muscles. Peak force output for each condition was also measured. Results: Significant effects by condition were found with planned comparisons revealing statistically significant differences for peak sEMG amplitude for TB in addition to peak force between BP and ISO45, ISO90, and ISO135 (p < 0.05). Analyses revealed similar peak sEMG amplitude for PM and AD for BP and isometric conditions (p > 0.05). Conclusions: The present study suggests that a contralateral limb resisted training method could be an efficacious method of recruiting motor units and thus may catalyse muscle fibre adaptations in strength and hypertrophy. This novel method might have considerable application to coaches or trainers not wishing to transport large and heavy equipment or in microgravity environments.